"IMPROVING OF ORGANIZATIONAL STRUCTURES IN ERA OF GLOBALIZATION" - Tukhtabayev Abdurashid. (Scholar Express Journals, 2024)
In this article, you can read about improving of organizational structures in era of globalization
Keywords: Globalization; Organization; Structure